EFFECT OF FMRFAMIDE-LIKE PEPTIDES ON THE PHARYNGEAL MUSCLE OF NEMATODES - T. A. Maljutina; N. B. Terenina (Российский паразитологический журнал, 2016)
FMRFamide-like peptides play an important physiological role in the enteric nervous system of nematodes.This is confirmed by immunocytochemical data on the presence and localization of neuropeptides in the pharynx of parasitic nematode Ascaris suum; identification of flp-gene in free-living nematode Caenorhabditis elegans expressing in pharyngeal neurons of the nervous system and encoding a number of FMRFamide - like neuropeptides; high sensitivity of the radial muscle of the pharynx nematodes towards a variety of  FMRFamide - like neuropeptides isolated from the nematode tissues.This review is devoted to a comparative analysis of data on the effects of some relatively short FMRFamide - like neuropeptides isolated from the nematode tissues, on pharyngeal pumping behavior in parasitic and free-living nematodes.The question about the possible use of some neuropeptides as potential anthelmintics inhibiting or completely turning off the work of the pharyngeal pump in parasitic nematodes is being discussed.